Basic problems in legal regulation of digital assets: ex amples in the USA, EU, and Serbia - Nikolić Ljubica (Zbornik Radova Pravnog Fakulteta u Nišu)
Modern financial technologies (Financial Technologies, FinTech) have improved traditional finance, while concurrently building a fundamentally new financial alternative. The application of FinTech has created digital financial products that are legally regulated but many crypto products still remain outside the law. The cryptocurrency market is a digital decentralized system that operates according to its own rules that users voluntarily accept, using personalized digital transactions. The application of FinTech in banking is a legal activity of banks aimed at strengthening competitive advantages in providing financial services, whereas central banks may require from commercial banks to upgrade or improve part of their digital technologies. In contrast, Blockchain technology has created a digital financial alternative which allows individuals to directly manage their digital wallets via phones and computers, without centralized control and outside of banking systems, by using the Internet and sharing original digital records among networked users worldwide. In the initial period, Blockchain technology generated resistance and was ignored by state regulatory bodies. The process of legal regulation of digital products and markets which were created on the basis of Blockchain and other digital technologies began after several years of actual Blockchain technology application. The subject matter of analysis in this paper is the legal regulation of already developed and widely used digital markets and assets, with specific reference to the legal solutions in the USA, the EU, and Serbia. The challenges of legal regulation of digital assets are numerous, ranging from insufficient knowledge of digital technologies to the unfeasibility of norming the decentralized digital segments. Thus, it is essential for the creators of law and the persons who apply the law to have the basic knowledge of modern digital technologies.